Corrigendum to âEnhanced lignin extraction and optimisation from oil palm biomass using neural network modellingâ Fuel 293 (2021) 120485 (Fuel (2021) 293, (S0016236121003616), (10.1016/j.fuel.2021.120485)) - Rashid, T. (Elsevier Ltd, 2022)
The author Syed Ali Ammar Taqvi shows an affiliation with âNeurocomputation Lab, National Centre of Artificial Intelligence, NED University of Engineering and Technology, 75270 Karachi, Pakistanâ which has been incorrectly added. Syed Ali Ammar Taqvi only has one affiliation with the Department of Chemical Engineering, NED University of Engineering and Technology Karachi, Pakistan. The authors would like to apologise for any inconvenience caused. Â© 2021 Elsevier Ltd